2005
DOI: 10.1007/s00122-005-2011-y
|View full text |Cite
|
Sign up to set email alerts
|

Fertility restorer locus Rf1 of sorghum (Sorghum bicolor L.) encodes a pentatricopeptide repeat protein not present in the colinear region of rice chromosome 12

Abstract: With an aim to clone the sorghum fertility restorer gene Rf1, a high-resolution genetic and physical map of the locus was constructed. The Rf1 locus was resolved to a 32-kb region spanning four open reading frames: a plasma membrane Ca(2+)-ATPase, a cyclin D-1, an unknown protein, and a pentatricopeptide repeat (PPR13) gene family member. An approximately 19-kb region spanning the cyclin D-1 and unknown protein genes was completely conserved between sterile and fertile plants as was the sequence spanning the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
95
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(96 citation statements)
references
References 57 publications
0
95
0
1
Order By: Relevance
“…Nuclear fertility restorer genes have been the focus of intense investigation over the past few years, with five recently cloned restorer loci shown to contain pentatricopeptide repeats (2,(22)(23)(24)(25)(26). Pentatricopeptide repeat proteins, numbering over 400 in Arabidopsis, are thought to be involved in transcript processing events within the mitochondrial and plastid genomes and, in the case of fertility restoration, likely direct processing of CMS-associated transcripts (27).…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear fertility restorer genes have been the focus of intense investigation over the past few years, with five recently cloned restorer loci shown to contain pentatricopeptide repeats (2,(22)(23)(24)(25)(26). Pentatricopeptide repeat proteins, numbering over 400 in Arabidopsis, are thought to be involved in transcript processing events within the mitochondrial and plastid genomes and, in the case of fertility restoration, likely direct processing of CMS-associated transcripts (27).…”
Section: Discussionmentioning
confidence: 99%
“…In the last years, several Rf genes were cloned from various crop species and the majority of them encode proteins belonging to the pentatricopeptide repeat family (PPR) (summarized in Table 1). 6,[12][13][14][15][16][17] All these restoring PPR proteins (hereafter called Rf-PPR) were shown to target the mitochondrion and act by specifically reducing the accumulation of their cognate CMS-associated mitochondrial RNAs and/or proteins. The prevalence of PPR proteins in plastid and mitochondrial RNA processing is now largely documented 18 and the fact that many Rf genes were found to encode PPR proteins is coherent CMS/Rf systems to serve as precious models to study nucleomitochondrial genetic interactions in plants.…”
Section: The Rf and Rf-like Ppr In Higher Plants A Fast-evolving Submentioning
confidence: 99%
“…46 In sorghum, the Rf1 gene which restores CMS to the A1 cytoplasm was also tentatively cloned by high-resolution mapping. 16,47 The Rf1 locus was delimited to a 32-kb region containing four ORFs among which the PPR13 gene represents the best gene candidate supporting fertility restoration activity. Opposite to all known Rf-PPR genes, PPR13 encodes a PPR protein belonging to the PLS subgroup and contains 14 PPR repeats as well as a C-terminal E motif.…”
Section: Characterized Arabidopsis Rf-like Pprs Are Involved In Mitocmentioning
confidence: 99%
“…Gene descriptions and gene family IDs were recovered from GreenPhyl (Rouard et al 2011) (Klein et al 2005). Nevertheless, the combined observations in barley and sorghum indicate that restorer genes can be found outside the Rf-like clade of PPR proteins identified by Fujii (Fujii et al 2011a, b;Dahan and Mireau 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the Rf genes known to date share common characteristics, even across highly divergent species including both monocots and dicots. Apart from some notable exceptions (Liu et al 2001;Klein et al 2005;Matsuhira et al 2012), most Rf genes identified so far encode pentatricopeptide repeat (PPR) proteins (Dahan and Mireau 2013;Gaborieau and Brown 2016). PPR proteins are characterized by tandem repetitions of the PPR motif, a 35 amino acid degenerate motif that forms a helixturn-helix structure (Howard et al 2012;Ban et al 2013;Ke et al 2013;Shen et al 2016).…”
Section: Introductionmentioning
confidence: 99%